Habitat Assessment for the Spiny Red Gurnard Chelidonichthys spinosus Using Habitat Suitability Index in the East China Sea and Southern Yellow Sea - Hanye Zhang; Zunlei Liu; Xiaojing Song; Jiahua Cheng; Jianzhong Ling (Diversity)
Chelidonichthys spinosus is a common fish distributed in the Northwest Pacific. To ensure sustainable utilization, it is crucial to understand the potential impacts of environmental changes on habitat suitability. A habitat suitability index (HSI) model was developed for C. spinosus based on seasonal bottom trawling survey data and remote-sensing oceanographic data collected in the East China Sea and southern Yellow Sea from 2015 to 2017. The model examined the relationships between the spatio-temporal distribution of fish and environmental variables. The suitable ranges of sea bottom temperature, sea bottom salinity, depth and chlorophyll-a for C. spinosus in four seasons were identified. Each variable was then combined into the HSI model with weights defined by the Gradient Boosting Regression Tree. The spatial distribution and the centroid of the HSI revealed that C. spinosus exhibits a seasonal southward and southwestward migratory pattern throughout the year. This migration pattern indicates the suitable habitats for reproductive, feeding, and overwintering activities. The conservation of C. spinosus resources is a matter of great urgency, and some of the feasible proposals have been put forth in this purpose.